Ex vivo model exhibits protective effects of sesamin against destruction of cartilage induced with a combination of tumor necrosis factor-alpha and oncostatin M - Manatsanan Khansai (2018)
© 2016 The Author(s). Background: Rheumatoid arthritis (RA) is an autoimmune disease associated with chronic inflammatory arthritis. TNF-α and OSM are pro-inflammatory cytokines that play a key role in RA progression. Thus, reducing the effects of both cytokines is practical in order to relieve the progression of the disease. This current study is interested in sesamin, an active compound in sesame seeds. Sesamin has been shown to be a chondroprotective agent in osteoarthritis models. Here, we have evaluated a porcine cartilage explant as a cartilage degradation model related to RA induced by TNF-α and/or OSM in order to investigate the effects of sesamin on TNF-α and OSM in the cartilage degradation model. Methods: A porcine cartilage explant was induced with a combination of TNF-α and OSM (test group) or IL-1β and OSM (control group) followed by a co-treatment of sesamin over a long-term period (35 days). After which, the tested explants were analyzed for indications of both the remaining and the degradation aspects using glycosaminoglycan and collagen as an indicator. Results: The combination of TNF-α and OSM promoted cartilage degradation more than either TNF-α or OSM alone and was comparable with the combination of IL-1β and OSM. Sesamin could be offering protection against cartilage degradation by reducing GAGs and collagen turnover in the generated model. Conclusions: Sesamin might be a promising agent as an alternative treatment for RA patients. Furthermore, the generated model revealed itself to be an impressive test model for the analysis of phytochemical substances against the cartilage degradation model for RA. The model could be used to test for the prevention of cartilage degradation in other biological agents induced with TNF-α and OSM as well.